Experiments On South Sulawesi Petanque Athletes on Hypnotherapy For Anxiety - Badaru, Benny; Nurulita, Retno Farhana; Suwardi, Suwardi; Hasanuddin, M. Imran (Sekolah Tinggi Olahraga dan Kesehatan Bina Guna, 2024)
In Indonesia, petanque is a game sport that has just emerged, especially in South Sulawesi Province. In this very complex game, players do not need to worry too much before and during the game. The aim of this study was to determine whether the use of hypnotherapy could help South Sulawesi Petanque athletes reduce excessive levels of anxiety. The method in this research uses the one-group pretest-posttest design. The sampling technique used purposive sampling and the research sample consisted of 15 athletes. . The instrument for measuring athletes' anxiety disorders uses the HARS (Hamilton Anxiety Rating Scale) questionnaire. The results of the study show that petanque athletes use hypnotherapy. The research results showed that South Sulawesi petanque athletes who used hypnotherapy became more confident, more relaxed, better able to control their emotions, and were able to change high anxiety into awareness when competing.